Holmium Oxide Film as a Saturable Absorber for 2 μm Q-Switched Fiber Laser - Rahman, Mohd Fauzi Ab; Rusdi, Muhammad Farid Mohd; Lokman, Muhammad Quisar; Mahyuddin, Mohamad Badrol Hisyam; Latiff, Anas Abdul; Rosol, Ahmad Haziq Aiman; Dimyati, Kaharudin; Harun, Sulaiman Wadi (IOP Publishing, 2017)
This work reports on the use of the holmium oxide (Ho2 O3) polymer film as a saturable absorber (SA) for generating stable Q-switching pulses operating in a 2-μm region in a thulium-doped fiber laser cavity. The SA is prepared by diluting a commercial Ho2 O3 powder and then mixing it with polyvinyl alcohol (PVA) solution to form a Ho2 O3 -PVA film. A tiny part of the film about 1 mm×1 mm in size is sandwiched between two fiber ferrules with the help of index matching gel. When incorporated in a laser cavity driven by a 1552-nm pump, stable Q-switching pulses are observed at 1955 nm within the pump power range of 363-491 mW. As the pump power increases within this range, the repetition rate rises from 26 kHz to 39 kHz, as the pulse width drops from 4.22 μs to 2.57 μs. The laser operates with a signal-to-noise ratio of 47 dB, and the maximum output power and the pulse energy obtained are 2.67 mW and 69 nJ, respectively. Our results successfully demonstrate that the Ho2 O3 film can be used as a passive SA to generate a 2-μm pulse laser.